Analysis of Water Quality and Phagocytic Activity (Clarias Sp.) in Aquaponic and Non-Aquaponic Cultivation Systems - Punto Apri Sembodo; Asus Maizar Suryanto Hertika; Yuni Kilawati (Postgraduate, University of Mataram, 2023)
Catfish (Clarias sp.) is one of the many fishery biota that has animal protein which is much loved by Indonesian people. One way to develop environmentally friendly catfish cultivation is through the implementation of an aquaponic biofilter system. This research aims to analyze physical, chemical, and biological water quality parameters in catfish cultivation with and without aquaponics, to obtain a description of the non-specific immune system which is analyzed from the conditions of phagocytic activity of catfish cultivated with and without aquaponics. The method used is by taking samples ten times per week by taking water quality parameters as well as blood samples of catfish raised in ponds with and without aquaponics. The analysis used is the unpaired T-test. Based on the results obtained, it was concluded that all parameters showed that the aquaponic cultivation media was better compared to those without aquaponics.